Evaluasi Strategis KWT Barokah dengan Pendekatan SWOT dan IFE-EFE di Kampung Cassava - Novi Syahara; Hananissa Carisa Aqila; Dinda Mutiara Hrp; Aditya Nur Zikrillah; Muhamad Gusti Pramadya (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The Barokah Women Farmers Group (KWT) in Kampoeng Cassava plays an important role in increasing the added value of cassava through processed food products while supporting community economic empowerment. However, business development still faces various internal weaknesses and external challenges that may hinder competitiveness and business sustainability. This study aims to formulate a business development strategy for KWT Barokah by identifying internal and external factors affecting business performance. The research employed a quantitative descriptive method using SWOT analysis supported by the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. The results showed an IFE score of 3.07 and an EFE score of 2.93, indicating that KWT Barokah has strong internal conditions and is capable of responding effectively to external opportunities. The Strength–Weakness (S–W) coordinate value of 1.31 and Opportunity–Threat (O–T) value of 1.01 positioned the business in Quadrant I, indicating that the appropriate strategy is the Strength–Opportunity (SO) strategy. The recommended strategies include increasing production capacity, developing product innovation, optimizing digital marketing, and strengthening organizational management and member participation to support business sustainability and improve competitiveness